Salmonella Strain Specificity Determines Post-typhoid Central Nervous System Complications: Intervention by Lactiplantibacillus plantarum at Gut-Brain Axis - Kaur, Amrita; Chopra, Kanwaljit; Kaur, Indu Pal; Rishi, Praveen (Frontiers in Microbiology, 2020)
Neurological complications occurring due to Salmonella infection in some typhoid patients remains a relatively unexplored serious complication. This study firstly aimed to explore whether disseminative ability of Salmonella from gut to brain is strain specific or not and on the basis of bacterial load, histopathology and behavioural changes it was observed that Salmonella enterica serovar Typhimurium NCTC 74 did not cause brain infection in murine model in contrast to Salmonella Typhimurium SL1344. Simultaneously, alarming escalation in antimicrobial resistance, making the existing antibiotics treatment inefficacious, prompted us to evaluate other bio-compatible strategies as a potential treatment option. In this context, role of gut microbiota in influencing behavior, brain neurochemistry and physiology by modulating key molecules associated with gut-brain axis has captured the interest of the scientific community. Followed by in-vitro screening of potential probiotic strains for beneficial attributes, efficacy of the selected strain was systematically evaluated at various levels of gut-brain axis against Salmonella induced brain infection. Analysis of behavioural (depression, anxiety, locomotor), neurochemical (gamma amino butyric acid, acetylcholinesterase), neuropathological (brain and intestinal histology; bacterial burden) and immuno-histochemical studies (tight junction proteins expression) revealed its role in preventing serious manifestations and proving its potential as ‘psychobiotic’. To the best of our knowledge, this is the first report elaborating strain specificity of Salmonella in causing post-typhoidal neurological manifestations and simultaneous use of probiotic in managing the same by influencing the pathophysiology at gut-brain axis.